Facial Involuntary Movements and Respiratory Failure in CANOMAD, Responsive to IVIG Therapy - Kate Johnson; Ashish Malkan; Mohamed Shaffi (Case Reports in Medicine)
CANOMAD is a rare chronic neuropathy, characterized by chronic sensory ataxia and intermittent brain stem symptoms due to antidisialosyl antibodies. The disorder results in significant morbidity but is poorly understood and often misdiagnosed. We describe a unique case of CANOMAD, associated with involuntary movements of the face; patient reported exacerbations with citrus and chocolate and respiratory muscle weakness. Our patient was initially misdiagnosed with Miller Fisher Syndrome, highlighting the need for vigilance should neurological symptoms recur in patients initially diagnosed with a Guillain Barre variant. Moreover, the optimal treatment is unknown. This patient responded remarkably to intravenous immunoglobulin and has been maintained on this treatment, without further exacerbations.